Probiotic Paenibacillus polymyxa HGA4C and Bacillus licheniformis HGA8B combination improved growth performance, enzymatic profile, gene expression and disease resistance in Oreochromisniloticus. (January 2023) - Midhun Sebastian Jose; Arun, Damodaran; Neethu, Sahadevan; Radhakrishnan, E.K.; Jyothis, Mathew
Abstract: Bacterial consortium containing two bacterial strains such as Paenibacillus polymyxa HGA4C and Bacillus licheniformis HGA8B incorporated in the diet of Oreochromis niloticus at a concentration of 1 × 10 6  CFU g −1 (PB1) and 1 × 10 8  CFU g −1 (PB2) revealed the probiotic potentials of the bacterial combination. The probiotic feed enhanced the growth performance, digestive enzymes, and antioxidant enzymes in the liver and intestine. Probiotic mediated growth enhancement was further substantiated by the up-regulation of genes such as GHR-1, GHR-2, IGF-1, and IGF-2 and the up-regulation of immune-related genes viz. TLR-2, IL-10, and TNF-α were also significantly modulated by probiotics supplementation. The intestinal MUC 2 gene expression revealed the mucosal remodification and the disease resistance of the fish challenged with Aeromonas hydrophila (MTCC-1739) was improved by the probiotic supplementation. Based on these results the new probiotic supplementation feed can be possibly marketed to help aquaculture farmers to alleviate many of the problems associated with fish farming. Graphical abstract: Image 1 Highlights: Consortia of bacteria modulated growth and biochemical parameters of Oreochromis niloticus. Demonstrated mechanism of growth and immune functioning by probiotic. Probiotics modulated expression of GHR-1, GHR-2, IGF-1 and IGF-2 genes. Bacteria increased the expression of MUC-2, TLR-2, IL-8, TNF-α and IL-10 genes. Intestinal MUC 2 up-regulation showed mucosal remodeling in the fish.